Analisis Pengaruh Kualitas Produk dan Strategi Harga terhadap Kepuasan Pelanggan, dan Pengaruhnya pada Terbentuknya Word-of-mouth di Perumahan Madani Group Jabodetabek - Irwanto, Agus; Rohman, Fatchur; Noermijati (Universitas Brawijaya, Indonesia, 2013)
This research had the purpose to analyze the effect of quality product, competitive strategypricing, on the satisfaction customer and create word of mouth on customer housing madani group. Respondentsin this research were are customer live in house madani group amounted to 92 persons. Datawere are analyzed used Partial Least Square (PLS). Result of this research he results showed a positiveinfluence quality product and significant impact on customer satisfaction, strategy pricing, and a significantpositive effect on Customer satisfaction has positive and significant impact on positive WOM satisfaction.